An Obligation To Manage Community Plantation (Plasma Plantation) From 20% Of The Plantation Company's Land Area - Enos Bonar Hasudungan Lumban Tobing; Abdul Razak Nasution (SEAN Institute, 2022)
Because regulation legislation, is obligation for possible development garden Public around (garden plasma) as big 20 percent from large land company plantation through partnership (garden plasma) with Public around. There is provision obligation allocate at least 20% from large area plantation for development garden people contain meaning connection law or decision which principled that area the owned by company plantation and results activity plantation no only owned by company plantation and used by they. However, company culture must intertwine partnership with Public in form culture plasma. Part from reform agrarian is distribution soil, which aim for increase ownership soil and ownership social for reach progress economy and ensure even distribution which more big. By because that, program landreform which oblige Public plantation for push development garden Public local on at least 20% from land Public around plantation Public in form partnership (plantation plasma) could Becomes wrong one method for reach Thing the with give this. equality and security. Law for arrange and arrange Public.